Penjaminan Kualitas Sistem Informasi Kalkulator Kredit Aktivitas Kemahasiswaan (KAK) Berbasis Web Menggunakan Standar ISO/IEC 29119 - Gilang Rama Permana; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2025)
This study aims to ensure the software quality of the web-based information system application, namely the Kredit Aktivitas Kemahasiswaan (KAK) Calculator of Pamulang University. The quality of this application is crucial as it directly relates to the non-academic graduation requirements for students. The methodology employed is structured Quality Assurance (QA), adopting the international standard testing framework ISO/IEC 29119 and referencing the quality characteristics of ISO/IEC 25010 (specifically Functional Suitability, Reliability, and Usability). Testing was performed using Blackbox Testing and Whitebox Testing techniques by designing and executing 25 comprehensive Test Cases. The test results showed that all 25 Test Cases were Passed (100% success rate), which validates the accuracy of the KAK point calculation , the reliability of the history management, and the interface responsiveness. With Zero Defects found in core functionality, the KAK Calculator application is declared compliant with the established quality standards and is accepted for use.